Comparing Organizational Culture: Perspectives from Western and Eastern Contexts - Widiastuti Widiastuti; Setyabudi Indartono; Nurus Sa'adah (International Journal of Magistravitae Management, 2023)
The relationship between employees and customers is shaped by organizational culture, which enables organizations to adapt and align with their goals and strategies. It includes a shared framework of meaning that sets one organization apart. A smaller percentage (25%) of researchers use a qualitative design, while the majority (65%) use a quantitative design. 10% of articles that are published use mixed methods. Online surveys (73%) and interviews (13%) are the most popular research methods, with observation (2%) and unspecified survey methods (10%) being less common. Employed people make up the majority of the research samples (75%), followed by businesses (18%), unemployed people (5%), and nations (3%). This study aims to compare the perspectives of Western and Eastern organizational cultures, investigate the benefits and drawbacks of each perspective, and identify which culture is more likely to produce successful organizational outcomes. While Eastern organizational culture is hierarchical and emphasizes teamwork, Western organizational culture emphasizes individual work systems and adherence to system rules. As a result, compared to Western cultural contexts, Eastern cultural contexts tend to emphasize teamwork more.